(untitled) (Educação e Pesquisa, 2015)
This article was produced for a special session of Associação Nacional de Pós-Graduação e Pesquisa em Educação (ANPED – National Association of Graduate Studies and Research on Education) about the relationship between philosophy, history, psychology and sociology of education. It first discusses the familiarity between philosophy and education, pointing their original bond, initiated in the Greek world under the rubric of foundations of education, and then explains a movement of withdrawal caused by the scientification of pedagogy. As a result of the advancement of modernization processes and the success of scientific knowledge, the area of foundations suffers the impacts of scientific rationality, which produces increasingly indisputable results and deprives metaphysical knowledge. Although this impact has not disallowed the dismissal of philosophy, it has led to a conceptual change and altered its role in relation to education and culture. The area then takes a more humble position in the face of science and other symbolic expressions, dialoguing about and interpreting the paradoxes and tensions generated by our relations with the world. From this approach, the article offers two suggestions for the relation between philosophy and education. Based on the hermeneutics of Hans-Georg Gadamer and on the transversal rationality of Wolfgang Welsch, the first suggestion resumes the perspective of the new scientific dialogues called interdisciplinarity as a way of overcoming the limits of specialization and meeting the complexity of educational issues. In the second suggestion, I indicate Hans Ulrich Gumbrecht’s position on the relevance of the humanities to develop risky thinking that is able to produce complexities in the analyses that illuminate educational issues.